Novel Compound Heterozygous Variants in Trans-2,3-Enoyl-Coenzyme A Reductase-Like Gene Associated With Catecholaminergic Polymorphic Ventricular Tachycardia - Keiko Shimamoto, MD, PhD; Naokata Sumitomo, MD, PhD; Taisuke Nabeshima, MD, PhD; Seiko Ohno, MD, PhD; Wataru Shimizu, MD, PhD; Kengo Kusano, MD, PhD; Takeshi Aiba, MD, PhD (JACC: Case Reports, 2024)
A 10-year-old female patient experienced syncope while swimming, and electrocardiography revealed polymorphic ventricular tachycardia, leading to a diagnosis of catecholaminergic polymorphic ventricular tachycardia. No pathogenic variant was identified in RYR2. Additional comprehensive genetic testing revealed novel compound heterozygous variants in trans-2,3-enoyl-coenzyme A reductase–like gene, which caused a recessive form of catecholaminergic polymorphic ventricular tachycardia.